SDG'S POST-PANDEMIC ECONOMIC DEVELOPMENT STRATEGY - Syakif, Reza; Radensyah, Muhamad; Nurhayati, Nurhayati; Naura, Naura; Putri, Aning Kesuma (Univesitas Muhammadiyah Tangerang, 2025)
This study examines the role of Sustainable Development Goals (SDGs) in shaping economic growth and labor absorption post-pandemic in Indonesia. It explores the challenges and strategies for achieving economic sustainability, particularly in sectors like agriculture, digital innovation, and education. Through a qualitative approach, this research analyzes key factors such as government policies, the rise of digital platforms, and the importance of critical thinking and ecoliteracy in fostering sustainable practices. The study highlights how platforms like Liniku.id, a digital agricultural tool, contribute to improving farmer literacy, enhancing agricultural productivity, and advancing SDG targets. The findings suggest that the integration of digital technologies and social innovations has a significant impact on empowering local communities, especially in rural areas. Furthermore, this paper underscores the importance of collaborative efforts from all stakeholders, including the government, private sector, and communities, to achieve the SDGs. The research concludes with recommendations for future initiatives, focusing on strengthening digital literacy among rural populations and expanding policy support for inclusive and sustainable economic development. The implications of this study are vital for policymakers, development agencies, and researchers aiming to contribute to Indonesia’s sustainable growth in alignment with the SDGs.